A rare case of Pseudomonas putida ventriculitis in intensive care unit: A case report - Mokhtar, Mohammad Nizam; Azaharuddin, Izzuddin; Abdullah, Farah Hanim; Izaham, Azarinah; Abdul Rahman, Raha (Frontiers in Medicine, 2022)
Pseudomonas putida is a rare pathogen leading to nosocomial and central nervous system infections. Despite having a low virulence and being a rare organism to cause bacteremia, it can evolve into a multidrug-resistant organism and lead to mortality and morbidity in the intensive care setting. A 64-year-old male gardener was presented with extensive acute subarachnoid hemorrhage with intraventricular extension causing hydrocephalus requiring embolization and coiling following a cerebral angiogram, which showed bilateral posterior circulation aneurysm and left anterior circulation aneurysm. External ventricular drain (EVD) was inserted given the worsening hydrocephalus. During his stay in the intensive care unit (ICU), he was becoming more septic and a full septic workup including a cerebral spinal fluid culture taken from the indwelling catheter of the EVD and was found to be positive for a ceftazidime-sensitive strain of P. putida. Following the treatment with intravenous ceftazidime for 1 week and a revision of the EVD on day 32 of admission, he continued to recover well and showed an improvement in his Glasgow Coma Scale (GCS) and septic parameters. Eventually, he was able to wean off mechanical ventilation. He was discharged from ICU care to the neurosurgical ward with supplemental oxygen on day 42 of admission. It is necessary to be aware of the possibility of nosocomial P. putida infection, especially in patients with indwelling catheters, and to consider the early initiation of appropriate antibiotic regimens once detected as well as strict precautions in hygiene during the management of these patients to avoid further development of multi-drug resistant (MDR) strains.